Media pressure and the process of Westernization in the context of body self-assessment among young heterosexual and gay Polish men - Bernadetta Izydorczyk; Małgorzata Lipowska; Sebastian Lizińczyk; Mariusz Lipowski; Jakub Wojtas (PLoS ONE, 2022)
Mass media and social networks portray a unified image of the perfect male body. The intensity and universality of this influence is an important element of the process of Westernization, especially in traditional cultures such as that of Poland. The main aim of the present study was to investigate the differences between Polish gay and heterosexual men in terms of the role played by self-esteem and the level of internalization of sociocultural standards of body appearance as predictors of the development of their body images. The research study was conducted by reference to 19- to 29-year-old Polish heterosexual (n = 287) and gay (n = 97) men. The variables were measured using Polish versions of the Sociocultural Attitudes towards Appearance Scale-3, the Self-Esteem Scale, and the Multidimensional Body–Self Relations Questionnaire. Statistical analyses identified several variables as the main predictors of body image in both heterosexual and gay young men: self-esteem, information-seeking, perceived pressure and the internalization of sociocultural standards regarding an athletic body image drawn from mass media. The only significant difference between the two groups was the fact that self-esteem, perceived pressure and the internalization of sociocultural standards from mass media did not play a predictive role with respect to Appearance Orientation among the group of gay men.